1991
DOI: 10.1007/bf00198431
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on entrainment in an annulus with and without velocity gradient across the density interface

Abstract: Abstract. The entrainment process in a two layer density stratified fluid column was studied experimentally by imposing external shear stress on one or both layers. The experiments have been conducted in an annular tank containing two water layers of different salt concentration and the shear stress was applied by means of rotating screens. The following quantities were measured: the screen velocity (which was kept constant during each experiment), the stress at the upper screen, and vertical profiles of circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The measurements of E and Hopfinger (1986) supported the value of the exponent n-~l.5, but Nokes (1988) performed detailed experiments resulting in n-~ 1.2. This result was also obtained by Chai and Kit (1991) in their special shear-free annulus experiments (for details see below).…”
Section: Ectri-"supporting
confidence: 76%
See 4 more Smart Citations
“…The measurements of E and Hopfinger (1986) supported the value of the exponent n-~l.5, but Nokes (1988) performed detailed experiments resulting in n-~ 1.2. This result was also obtained by Chai and Kit (1991) in their special shear-free annulus experiments (for details see below).…”
Section: Ectri-"supporting
confidence: 76%
“…The Richardson number was based on the same friction velocity and on the thickness of the upper mixed layer. The experimental results of Scranton and Lindberg (1983) and Chai and Kit (1991), have shown that when the interface is exposed to a velocity shear, the exponent of the entrainment law (1) is close to 1.8. The results of Kantha et al (1977) for moderate and large Richardson numbers, follow approximately the same power law (see Chai and Kit 1991, Fig.…”
Section: Ectri-"mentioning
confidence: 96%
See 3 more Smart Citations